Pendampingan serta Perencanaan Jembatan Desa Sungai Waluh di Desa Kabunan Kabupaten Pemalang - Budiono Joko Nugroho; Arief Kusbiantoro; Victor Victor (Universitas 45 Surabaya, 2024)
Kabunan Village, Taman District, Pemalang Regency, built a village bridge with a width of 3.2 meters and a length of 65 meters in Kabunan Village to shorten travel time, where residents usually have to pass the Kabunan Bridge which is 500 meters from the planned position of the village bridge. With the assistance and planning carried out by the Civil Engineering Lecturer of the 17 August University, Budiono Joko Nugroho and the Civil Engineering Lecturer of the Semarang State University, Arief Kusbiantoro, so that the stages of bridge design planning and construction implementation run well according to applicable regulations and provisions. With the bridge construction permit issued by the Central Java Pusdataru, it is hoped that the construction of the village bridge will run well and smoothly.